The Role of Agricultural Counsels’ Performance in Shaping Rice Farmers' Satisfaction and Behavior: A Regional Study in East Java, Indonesia - Faisol Humaidi; Teguh Soedarto; Mubarokah; Nuriah Yuliati (Postgraduate, University of Mataram, 2025)
This study examines the role of agricultural counselors' performance in shaping rice farmers' satisfaction and behavior in East Java, Indonesia. Agricultural extension is central to national agricultural development, as counselors act as facilitators, motivators, and change agents who bridge knowledge and technology to farmers. Using a survey of 215 agricultural counselors and 215 rice farmers across Pacitan, Nganjuk, and Lamongan, data were collected through validated questionnaires and analyzed with SEM-PLS. The findings reveal that counselor performance is significantly influenced by job satisfaction, competence, motivation, and independence, while individual characteristics contribute less. Among these, job satisfaction shows the strongest effect, indicating that adequate facilities, supportive work environments, and fair compensation drive counselor effectiveness. Furthermore, counselor performance directly enhances farmers' behavior in adopting agricultural innovations and indirectly improves their satisfaction, particularly through improved yields and more consistent guidance. Farmers' satisfaction, in turn, fosters positive and proactive behaviors such as active participation and the application of extension recommendations. These results highlight that effective extension services depend not only on technical competence but also on psychological and organizational factors that motivate counselors and strengthen farmer trust. The study concludes that strengthening counselor performance is essential for sustainable agricultural development, farmer empowerment, and increased rice productivity.